The inherent antibiotic activity of myxobacteria-derived autofluorescent outer membrane vesicles is switched on and off by light stimulation - Lapuhs, Philipp; Heinrich, Eilien; Garcia, Ronald; Goes, Adriely; Frank, Nicolas; Bollenbach, Lukas; Stibane, Veronika; Kuhn, Thomas; Koch, Marcus; Kiemer, Alexandra K.; Müller, Rolf; Fuhrmann, Kathrin; et al. (Nanoscale, 2022)
Outer membrane vesicles are small, lipid-based vesicles shed from the outer membrane of Gram-negative bacteria. They are becoming increasingly recognised as important factors for resistance gene transfer, bacterial virulence factors and host cell modulation. The presence of pathogenic factors and antimicrobial compounds in bacterial vesicles has been proven in recent years, but it remains unclear, if and how environmental factors, such as light specifically regulate the vesicle composition. We report the first example of autofluorescent vesicles derived from non-pathogenic soil-living myxobacteria. These vesicles additionally showed inherent antibiotic activity, a property that is specifically regulated by light stimulation of the producing bacteria. Our data provide a central basis for better understanding the environmental impact on bacteria-derived vesicles, and design of future therapeutic options.
CRIS-Team Scopus Importer:2022-12-09